2017
DOI: 10.1155/2017/3080547
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Auricular Acupoint Stimulation in Overweight and Obese Adults: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials

Abstract: Objective To investigate the effect of auricular acupoint stimulation on overweight and obese adults. Methods We searched databases including PubMed, EMBASE, Allied and Complementary Medicine Database, National Knowledge Infrastructure, and the PerioPath Index to Taiwan Periodical Literature. The modified Jadad scale was used to assess study quality. We investigated the effect of auricular acupoint stimulation on anthropometric measurements. Results Eighteen randomized controlled trials (RCTs) were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 51 publications
(91 reference statements)
2
15
1
3
Order By: Relevance
“…As mentioned in the meta-analysis, combination of acupuncture and lifestyle modification is more effective compared with lifestyle modification alone [ 12 ]. Results of Yeh's research suggested that ear acupoint stimulation had remarkable improvements in the anthropometric parameters of Body Weight (BW), BMI, and so on [ 13 ]. In addition, another systematic review performed in 2015 has also shown that clinical efficacy of acupoint catgut embedding therapy was better than that of the control group for simple obesity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in the meta-analysis, combination of acupuncture and lifestyle modification is more effective compared with lifestyle modification alone [ 12 ]. Results of Yeh's research suggested that ear acupoint stimulation had remarkable improvements in the anthropometric parameters of Body Weight (BW), BMI, and so on [ 13 ]. In addition, another systematic review performed in 2015 has also shown that clinical efficacy of acupoint catgut embedding therapy was better than that of the control group for simple obesity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ear skin (locating in concha) has the greatest density of branches of the vagus nerves derived from the superior jugular ganglion of the vagus [ 7 ]. Therefore, application of auricular VNS or acupuncture in weight reduction is common, an effect mainly attributable to the suppressed appetite [ 8 11 ]. Recently, auricular VNS was reported to increase brown adipose tissue (BAT) activity [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the therapist and clients can develop a sense of closeness, trust, and confidence [20]. Several studies have shown promising results about the effect of ear acupressure on insomnia [20,22], menstrual cramps and dysmenorrhea [21,23,24], premenstrual pain [25], chemotherapy-induced nausea and vomiting [26], smoking cessation [27], obesity [18], and shortness of breath [28]. In the study of Oakley et al, acupuncture was affective in premenopausal women with sexual function [43].…”
Section: Discussionmentioning
confidence: 99%
“…The external ear is one of the several somatotopic microsystems that can be used in acupressure. Ear acupressure, also known as auriculotherapy or auricular acupressure [15,16], was first presented in ancient Chinese medicine (300 to 500 years BC), but Dr. Paul Nogier was the first Western physician who put forward auriculotherapy in a scientific way [13,17,18]. According to this theory, each part of the body is associated with a specific part of the ear that reflects the physiological or pathological state of the body [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation